A 6-week, phase IIb, randomized, double-blind, placebo-controlled trial of Anyu Peibo capsules for the treatment of major depressive disorder in adults - Shen He; Yimin Yu; Jingjing Huang; Jiahui Yin; Yajuan Niu; Yazhou Lu; Bin Wu; Maosheng Fang; Xue Wang; Zhiping Tao; Lehua Li; Kan Li; et al. (SAGE Publishing, 2023)
Background: Almost one-third of patients with major depressive disorder (MDD) do not respond to conventional antidepressants, and new treatments for MDD are urgently needed. Objectives: This phase IIb clinical trial was designed to evaluate the efficacy and safety of Anyu Peibo capsules in the treatment of adults with MDD. Design: A multicenter, randomized, double-blind, placebo-controlled, parallel-group, fixed-dose study. Methods: A total of 172 patients with MDD from nine study centers were randomized (1:1) to receive placebo ( n  = 86) or oral Anyu Peibo capsules (0.8 g) twice per day ( n  = 86) for 6 weeks. The primary endpoint was the change in the Montgomery Åsberg Depression Rating Scale (MADRS) total score from baseline to week 6, analyzed using an analysis of covariance (ANCOVA) approach with the baseline MADRS score, center effect and center by group interaction as the covariates. Other efficacy endpoints and variables included clinical response and remission rates according to the MADRS and the 17-item Hamilton Depression Rating Scale (HAMD-17) scores, the change in the HAMD-17, Clinical Global Impression - Severity scale and Clinical Global Impression - Improvement scale scores and the reduction in the Hamilton Anxiety Scale from baseline to week 6. Results: The mean baseline MADRS total scores were 29.20 and 29.72 in the Anyu Peibo ( n  = 82) and placebo groups ( n  = 81), respectively. The least squares mean change in the MADRS score from baseline to week 6 was 16.59 points in the Anyu Peibo group and 14.51 points in the placebo group. Although there were greater reductions in the MADRS score from baseline to week 6 in the Anyu Peibo capsule group compared to the placebo group, the difference did not reach statistical significance (least-squares mean difference, 2.07 points; 95% confidence interval, −0.27 to 4.41; p  = 0.0819). The results of sensitivity analyses by ANCOVA with the last observation carried forward method for missing data indicated that the administration of Anyu Peibo capsules may lead to a significant reduction in depressive symptoms compared to the placebo (least-squares mean difference: 3.29 points; 95% confidence interval: 0.64-5.93; p  = 0.0152). Furthermore, Anyu Peibo capsules showed significant benefits over placebo when the change in the HAMD-17 score from baseline to week 6 was evaluated as the secondary analysis ( t  = 2.01; 95% confidence interval, 0.03-4.23; p  = 0.0464). Conclusion: Anyu Peibo capsules may have an effective and safe antidepressant effect, which warrants further research.